Kedaulatan Rakyat’s daily survival strategies in the siege of digital media - Ispandriarno, Lukas (Penerbit Universiti Kebangsaan Malaysia, 2021)
Print media in the form of daily newspapers face a serious challenge with the presence of digital media. A number of print media organisations stopped publishing between 2005 and 2018. The challenges became more severe when the Covid-19 virus pandemic was declared to have existed in Indonesia since March 2020. This media economic study investigates the survival strategies of the Kedaulatan Rakyat newspaper. As the oldest newspaper in Indonesia and accompanying the birth of the Republic of Indonesia in 1945, the Kedaulatan Rakyat daily office, based in the city of Yogyakarta, has experienced economic difficulties such as the decline of readers, especially millennials. In addition, the acquisition of national advertising also fell by 75% while new/mini advertisements fell by around 50%. The author applied qualitative methods to extract data from in-depth interviews with two editors, two directors and one marketing communication officer. The results show several strategies implemented, including increasing the number of readers, intensifying advertorials, holding events, and reducing the number of pages. The desire of the owner to safeguard the family heritage also plays an important role in maintaining the continuity of the publication and the credibility of the paper.